The Influence Of The Make A Match Method For Mastering Mufradat At Al-Qur'an Middle School Salafiyyah Syafi'iyyah Sukorejo Bangorejo Banyuwangi - Alya Afifah Maliyanah; Munirul Abidin; Muhammad Ichsan (Program Studi Pendidikan Bahasa Arab, 2024)
Vocabulary teaching is an important aspect in language acquisition because mufradat is the key to the teaching and learning process. The researcher used the make a match method for mastery of mufradat at SMP Al-Qur'an Salafiyyah Syafi'iyyah Sukorejo Bangorejo Banyuwangi. The purpose of this study was to determine the effect and results of student learning using the make a match method for mufradat mastery at SMP Al-Qur'an Salafiyyah Syafi'iyyah Sukorejo Bangorejo Banyuwangi. This research method uses quantitative methods using Experimental with the research design using the One-Group Pretest-Posttest Design. The sample of the research was 15 grade 9 students of SMP Al-Qur'an. Data collection techniques using observation, interviews, documents, pretest and posttest. The results of the normality test, there is a normal distribution population that is used in the experimental post-test and control post-test. the results of the homogeneity test produce a sig value > 0.05 = homogeneous, meaning that the data is taken from the same population. And in the Paired T-Test there is a significant effect on the pretest and posttest classes, namely from an average of 77.00 it has increased to 82.33.